Meningkatkan Kemandirian dan Kreativitas Siswa dalam Pendidikan Kurikulum Merdeka - Nuriah, Chintia Inka; Silvia, Okta; Pratiwi, Putri Dwi Nanda; Sari, Selaras Royan; Rhomadoni, Syahrul; Zad, Tamam Fikri Khoiruz (Indonesian Journal Publisher, 2024)
An important aspect of the Merdeka Curriculum is differentiated learning, which recognizes individual differences in students and provides learning experiences according to their needs and interests. However, in its implementation, there are still many challenges, such as gaps in resource availability, changes in traditional mindsets in education, and the need to involve educators in developing learning strategies that encourage student independence and creativity. To encourage students' independence and creativity in the learning process, educators can use the project-based learning model. The method used in this article is a literature review. Data collection is obtained from scientific articles, journals, research reports, seminar proceedings, and websites relevant to the title. Based on the results and discussion, it can be concluded that project-based learning can increase student independence and creativity in independent curriculum education. Project based learning is a project-based learning that provides flexibility for students to explore the subject matter independently and in groups in creating ideas and ideas. This is in accordance with an important aspect of the Merdeka curriculum, namely differentiated learning, which recognizes.